2016
DOI: 10.1111/aas.12688
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Pain Scale – translation, reliability, and validity in a Swedish context

Abstract: Results of the Swedish version of the BPS support its use in critically ill patients who cannot self-report their pain level. Still, additional studies are needed to further explore its reliability and validity in the Swedish ICU context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The Behavioral Pain scale was originally in the French language, which was translated into English [19], Chinese [20], Finnish [21], Brazilian Portuguese [22], Swedish [23], and Persian [24]. The behavioural pain scale has three parts: facial expression, upper limb movement and Compliance with mechanical ventilation, each graded with scores 1-4.…”
Section: Resultsmentioning
confidence: 99%
“…The Behavioral Pain scale was originally in the French language, which was translated into English [19], Chinese [20], Finnish [21], Brazilian Portuguese [22], Swedish [23], and Persian [24]. The behavioural pain scale has three parts: facial expression, upper limb movement and Compliance with mechanical ventilation, each graded with scores 1-4.…”
Section: Resultsmentioning
confidence: 99%
“…The Swedish origin of ALPS is probably the most important reason for its widespread use in Sweden although only the neonatal version (ALPS‐neo) is validated to some extent . Some of the scales in use have been systematically translated and validated into Norwegian or Swedish , while others have not, but are still used in neonatal units (e.g. the Norwegian version of EDIN).…”
Section: Discussionmentioning
confidence: 99%
“…Finland (139), and Sweden (140). These studies reported good psychometric properties for the BPS, including satisfactory interrater reliability (135)(136)(137)(138)140), discriminant validity (135)(136)(137)(138)140), internal consistency (136)(137)(138), and test-retest reliability (136). In addition, the feasibility of the BPS has been evaluated.…”
Section: Choice Of Pain Assessment Toolsmentioning
confidence: 95%